Long-read sequencing of nascent RNA reveals coupling among RNA processing events - Herzel, Lydia (Genome Res, 2018)
Pre-mRNA splicing is accomplished by the spliceosome, a megadalton complex that assembles de novo on each intron. Because spliceosome assembly and catalysis occur cotranscriptionally, we hypothesized that introns are removed in the order of their transcription in genomes dominated by constitutive splicing. Remarkably little is known about splicing order and the regulatory potential of nascent transcript remodeling by splicing, due to the limitations of existing methods that focus on analysis of mature splicing products (mRNAs) rather than substrates and intermediates. Here, we overcome this obstacle through long-read RNA sequencing of nascent, multi-intron transcripts in the fission yeast Schizosaccharomyces pombe. Most multi-intron transcripts were fully spliced, consistent with rapid cotranscriptional splicing. However, an unexpectedly high proportion of transcripts were either fully spliced or fully unspliced, suggesting that splicing of any given intron is dependent on the splicing status of other introns in the transcript. Supporting this, mild inhibition of splicing by a temperature-sensitive mutation in prp2, the homolog of vertebrate U2AF65, increased the frequency of fully unspliced transcripts. Importantly, fully unspliced transcripts displayed transcriptional read-through at the polyA site and were degraded cotranscriptionally by the nuclear exosome. Finally, we show that cellular mRNA levels were reduced in genes with a high number of unspliced nascent transcripts during caffeine treatment, showing regulatory significance of cotranscriptional splicing. Therefore, overall splicing of individual nascent transcripts, 3′ end formation, and mRNA half-life depend on the splicing status of neighboring introns, suggesting crosstalk among spliceosomes and the polyA cleavage machinery during transcription elongation.